Parents’ Cultural Practices and Infant Mortality in Mangu Local Government Area of Plateau State, Nigeria - Shipurut, Geoffrey Nanbal; Opeyemi, Victoria Adeniyi; Ediba, Sabastine (Darul Yasin Al Sys, 2025)
Infant mortality remains a significant public health concern in Nigeria, with cultural practices playing a crucial role in child survival. This study examined parents’ cultural practices and infant mortality in Mangu Local Government Area of Plateau State, Nigeria. The study used a descriptive, cross-sectional survey research design. A sample size of 400 respondents was selected from the total population of 442,100 using the Tare Yamane formula. Questionnaires were distributed to 400 randomly selected participants across all the wards in Mangu LGA. Interviews were also conducted with six key informants to complement the data gathered from the questionnaires Responses from the questionnaires were analyzed using descriptive statistics of frequency counts and percentages. Qualitative data were analyzed while outlining the key point presented by the key informant. The study revealed that cultural practices, such as reliance on traditional herbs, beliefs in supernatural causes, and generational curses, significantly contribute to infant mortality in Mangu LGA by discouraging timely medical interventions. The study concludes that deep-rooted trust, affordability, and community influence sustain these practices, making it difficult for parents to fully embrace modern healthcare. The study recommended that enhancing healthcare access, educating communities on infant health, and collaborating with traditional leaders can bridge the gap between cultural practices and modern medical care, promoting timely and effective interventions.